Examples and Overaddressing in Bilingual Dictionaries. - Beyer, Herman L. (Lexikos, 2011)
Addressing equivalence prevails in a dictionary article when all the translation equivalents in the translation equivalent paradigm are represented in the target language examples in the cotext section and each target language example contains a translation equivalent that appears in the translation equivalent paradigm. The disruption of this equivalence takes place as a result of the procedures of underaddressing (when not all the translation equivalents in the translation equivalent paradigm are represented in the target language examples in the cotext section) and overaddressing (when target language examples contain translation equivalents that do not appear in the translation equivalent paradigm). In a polyfunctional bilingual dictionary addressing equivalence represents the ideal addressing structure between translation equivalent paradigm and cotext section. In Afrikaans bilingual dictionaries, addressing equivalence is rare, but this seems to be the case in bilingual dictionaries of other languages also. Although instances of underaddressing can be neutralised relatively easily, a deeper investigation into overaddressing has found that most target language examples that seem to be symptomatic of overaddressing indeed contribute to communicative equivalence in spite of a would-be deficient addressing structure. This is because these target language examples do not function as true examples (that illustrate the behaviour of translation equivalents), but are in fact cotextual specifiers that represent a functional procedure of contextual translation equivalent exclusion, through which the target user is advised of the non-usability of the translation equivalents offered in the translation equivalent paradigm in certain contexts. This finding requires a re-appreciation of addressing structures in general and the principle of addressing equivalence in particular.Keywords: addressing equivalence; addressing structure; communicative equivalence; context; contextual translation equivalent exclusion; contextualising entry; cotext entry; cotext section; cotext; cotextual illustrator; cotextual specifier; direct address; equivalent relation; example; false addressing; function; indirect address; lemma; overaddressing; polyfunctional bilingual dictionary; primary address; secondary address; source language cotext entry; target language cotext entry; translation equivalent paradigm; translation equivalent; true example; underaddressing